An adaptive network allocation vector timer-based carrier sense multiple access with collision avoidance medium access control protocol for underwater acoustic sensor networks - Md Arifur Rahman; Youngdoo Lee; Insoo Koo (International Journal of Distributed Sensor Networks)
Underwater sensor networks with acoustic communications are significantly challenged due to several unique characteristics, such as energy consumption, high propagation delay, and severely limited distance-dependent bandwidth. These unique characteristics make it difficult to directly adopt schemes for underwater acoustic sensor networks that are already proven for reliable terrestrial wireless sensor networks. In particular, propagation delay is one of the key elements for delay-sensitive underwater applications. In this article, we propose an adaptive network allocation vector timer–based underwater carrier sense multiple access with collision avoidance medium access control protocol with propagation delay estimation to maximize network throughput while reducing the end-to-end delay in transmission for delay-sensitive applications. In the proposed scheme, we first calculate the distance between the sensor nodes using received signal strength and the Lambert W function and then estimate the propagation delay. Consequently, the neighbor node can set an adaptive network allocation vector timer based on the estimated propagation delay. Our extensive simulation results reveal that the proposed scheme outperforms the distance-aware collision avoidance protocol, the propagation-delay-tolerant collision avoidance protocol, and the maximum propagation delay-based medium access control protocol in terms of network throughput and end-to-end delay. The simulation results also show that the proposed scheme has near-optimal performance compared to the knowledge-based medium access control scheme, which utilizes the location information of each sensor node.